NICOTIANA TABACUM TISSUE CULTURE AS A SOURCE OF POTATO VIRUS Y - Khasanov , V.T.; Alekseev , Ya.I.; Minakova , N.Yu.; Orazbaeva , G.K.; Beisembina , B.; Fida , M.A. (Eurasian Journal of Applied Biotechnology, 2014)
Finding alternative approaches to the technology of storage and purification of potato viruses in order to optimize the methods of their isolation is topical. In vitro cultivation of plant callus tissue with simultaneous accumulation of a virus allows its long time accumulation, precluding other virus’s infection. Besides, the isolation of viral antigen from callus tissue provides a highly purified antigen due to absence of many specific proteins and enough amount of antigen all year round. The purpose of our research was accumulation of potato virus Y (PVY) in plant culture tissues for further isolation and purification of viral antigen and producing specific antibodies. Accordingly, the potato virus Y was chosen as a focus of the research. Object of the research, Nicotiana tabacum Samsun variety served to accumulate the virus. This article presents results of potato virus Y (PVY) accumulation in Nicotiana Tabacum tissue culture and its further purification. Capability of culture tissue produced from PVY-inoculated plant (Nicotiana Tabacum) to accumulate and maintain viral infection for a long time was ascertained. Purity of commercial viral preparation, as well as PVY maintaining possibility in vitro in Cherie potato plant, inoculated plants of Nicotiana tabacum and callus induced from its regenerated plants in our research were proved using ELISA and PCR in real time. In another study, mouse polyclonal antibodies specified to the virus were produced and reacted with a 1/6400 titer of antigen.